Planos de carreira e remuneração do magistério em municípios paranaenses: dados sobre existência, atualização e transparência - Flach, Simone de Fátima (Revista Cocar, 2018)
O texto apresenta o percurso empreendido para o levantamento de dados e informações sobre a existência, atualização e transparência nos Planos de Carreira e Remuneração do Magistério Público em municípios paranaenses, tendo como referência as determinações das Leis nº 12.571/11, 9394/96, 11.738/08 e 13.005/14. Ainda, identifica algumas fragilidades das Prefeituras e Câmaras Municipais para o cumprimento da Lei de Acesso à Informação. Face à realidade paranaense. Conclui-se que a indisponibilidade de informações e documentos fragiliza análises mais consistentes a respeito da valorização dos profissionais do magistério público municipal. Palavras-chave: Planos de Carreira do Magistério. Valorização do Magistério. Políticas de valorização do Magistério. Magistério Público Municipal. Career plans and remuneration off magisterium in Paranáâ€™s cities data about update and make it public Abstract The text presents the route taken for collection of the data and information on the existence, update and transparency of career plans and remuneration of public teaching profession in Paraná cities, having as reference the following laws Nr. 12.571/11, 9394/96, 11.738/08 and 13.005/14. It also identifies some weaknesses of the City hall and City councils to fulfill the Information access law. It is concluded that the unavailability of information and documents weakens the more consistent analysis relative to the valorization of the teachers of municipal public teaching profession. Keywords: Teaching professionâ€™s career plans. Teaching professionâ€™s value. Policies of valorization of teaching profession. Municipal teaching profession.